Evaluation of different methods of securing cellophane bands for portosystemic shunt attenuation. Issue 1 (17th November 2018) - Joffe, Michelle Robyn; Hall, Evelyn; Tan, Christopher; Brunel, Laurencie
Abstract: Objective: To compare mechanisms of and pressures at failure of 4 methods of securing 2 types of cellophane bands around a vein. Study design: Ex vivo mechanical evaluation. Methods: Cellophane bands composed of 3 or 4 layers were applied around a cadaveric external jugular vein (EJV) to create 25% or 50% attenuation. These bands were secured with a medium or medium‐large polymer locking ligation clip (PLLC), or a medium or medium‐large titanium ligation clip (TLC). Sterile saline 0.9% was instilled into the lumen of the EJV until a pressure of 100 mm Hg was reached. Failure mechanism and luminal pressure at failure were compared between groups. Results: Medium clips failed less often than medium‐large clips ( P  < .001) and consistently sustained 100 mm Hg without failing. Three‐layer cellophane bands were 4.1 times more likely to fail than 4‐layer bands ( P  = .003, CI 1.6‐10.2) and failed at lower pressures (28.32 ± 3.59 mm Hg and 44.81 ± 6.51 mm Hg, respectively, P  = .027). Failure rates of the cellophane band constructs did not differ whether secured with PLLC or with TLC ( P  = .635) or with 25% vs 50% attenuation ( P  = .780). Conclusion: A single medium clip withstood physiological forces and secured a cellophane band at up to 50% attenuation. A 3‐layer cellophane band was more likely to fail compared with a 4‐layer cellophane band. Clinical significance: These ex vivo results provide evidence to support the application of a 4‐layer cellophane band secured with a single medium PLLC or TLC for portosystemic shunt attenuation. A single medium PLLC should be used to eliminate computed tomography artifacts during postoperative evaluation of shunt closure.